Effectiveness of PjBL on pgsd students’ ability to design social studies modules-based local wisdom - Nurul Sinta Nirwana; Safitri Yosita Ratri; Vera Yuli Erviana; Oktavian Muning Sayekti (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
The present study examines changes in PGSD students’ ability to design local wisdom-based social studies modules after participating in Project-Based Learning (PjBL). The study employed a quasi-experimental one-group pre–test–post–test design involving 42 fifth-semester students. The intervention consists of PjBL activities, including exploring local culture, designing collaborative projects, and engaging in reflective learning. Data were collected using pre- and post-tests, observations, and validated self-assessment instruments. Data were subsequently analyzed using paired-sample t-tests and N-Gain calculations. The results indicate a significant increase in students’ module design skills, particularly in content organization, integration of local wisdom, collaboration, and socio-cultural relevance (p < 0.001). These findings indicate that PjBL supports the development of more advanced skills in designing contextual learning modules.